The Delay and Costs of Diagnosing Systemic Vasculitis in a Tertiary-Level Clinic - Taimen Kirsi; Mustonen Anssi; Pirilä Laura (Springer, 2022)
Introduction
The diagnosis of systemic vasculitis is a challenge because of the heterogeneity of clinical manifestations. The aim of this study is to analyze the diagnostic delay in systemic vasculitis, the total costs during the first year of care, and how the diagnostic delay affects the costs in a tertiary health care facility.
Methods
Patients with a new diagnosis of systemic vasculitis between 2010 and 2018 were identified from hospital records. The diagnostic delay and health care costs were evaluated during the diagnostic period and within 12 months after the first contact with tertiary health care. Vasculitis-related costs were recorded as true costs charged. A total of 317 patients fulfilled the study criteria. The diagnoses were grouped into three clinically relevant groups: IgA vasculitis and other small-vessel vasculitis (n = 64), ANCA-associated vasculitis (AAV) (n = 112), and large-vessel vasculitis (LVV) (n = 141).
Results
The diagnostic delay from the first referral to tertiary-level clinic was shortest in the LVV group and longest in the AAV group. Total costs during the diagnostic period were the highest in the AAV group (median = €6754 [IQR €8812]) and lowest in the LVV group (median = €3123 [IQR €4517]), p < 0.001. There was a significant positive correlation between the diagnostic delay and total costs during the diagnostic period and 12 months (rs = 0.38, p < 0.001 and rs = 0.34, p < 0.001, respectively). In a linear model, the inpatient days and the number of laboratory tests were the strongest predictors (p < 0.001) of a higher treatment cost during the diagnostic period.
Conclusions
There is a substantial diagnostic delay that correlates significantly with the costs in tertiary-level health care when diagnosing systemic vasculitis.